A Model-Free PID Tuning to Slosh Control Using Simultaneous Perturbation Stochastic Approximation - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Falfazli, Mat Jusof; Mohd Helmi, Suid; Ahmad Nor Kasruddin, Nasir (2015)

(untitled)
This paper addresses an initial study of a modelfree PID tuning based on simultaneous perturbation stochastic approximation (SPSA) for liquid slosh control. The SPSA method is used to optimize the PID parameters such that the liquid slosh is minimized. In order to validate our modelfree design, a liquid slosh model is considered to represent the lateral slosh motion. The simulation results demonstrate that the proposed model-free method has a good potential in reducing the liquid slosh without explicitly modeling the liquid slosh behavior.